Aspirasi Pendidikan Anak Usia Dini Dalam Keluarga Hindu Di Desa Batuaji Kecamatan Kerambitan Tabanan - I Gusti Agung Putu Wahyu Pradnyana; I Ketut Sudarsana (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study aims to find out the Aspirations of Early Childhood Education in Hindu Families in Batuaji Village, Kerambitan District, Tabanan. The lack of public access to early childhood education is a serious problem because early childhood is the beginning of a generation of gold. The progress of a nation is determined by the quality of early childhood education. The method used in this study is qualitative with descriptive research types. The research location was in Batuaji Village, Kerambitan District, Tabanan Regency. The source of primary data is obtained by interviewing informants, secondary data sources are obtained from literature studies and documentation. Based on the results of research on the Aspirations of Early Childhood Education in Hindu Families in Batuaji Village, Kerambitan District, Tabanan Regency, the community's aspirations towards early childhood education for Hindu families in Batuaji Village are very good. The process of developing people's aspirations for early childhood education in Hindu families in Batuaji Village is by a) Disseminating PAUD benefits which include: Parents as Counselors, Parents as Educators and Parents as Successors of Descendants, b) Formation of Character of Children in Hindu Families includes: Teaching Ethics and Procedure of a child from an early age, Implementation of Birth Baby Ceremony, Implementation of Monthly Nelu Ceremony and Implementation of Ngotonin Ceremony, c) Enabling POSYANDU in Hindu family.